(3JMOjO fgGjGJ GdCeGcf hJUMjM eSGaGJ GdeSGcfs - (3eMeO Hf CMeO, CHh GdQjMGf GdHjQhfj GdNhGQRej,J (B440 (3g` s ((3ZRfI s)
(3ChdgG (B:s
(3HYO GdOjHGLg deG cGfJ GdYbhd eMJGLg Edi GdGSJeOGO hGdfahS ZjQ eSJZjHg Yf GdGSJQaGO s
(3BNQgG (B:s
(3hGddg JYGdi jYfi Ydi eG CfG ajg ef JUMjM GdMQcGJ GdSeGhjI HehGRg GdCQUGO agh GdeQZhH ai NjQg hKhGHg s
(3ajgG LOGhd hQShe gfOSjIs
(3hai BNQg ef faS GdjO haQZJ efg HZRfI HSHY Hbif ef QLH SfI SJ YTQg hCQHYeGFg hdYdg ef NW GdeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B314 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B205s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B476 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B13 s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdadcs